1970
DOI: 10.1037/h0029347
|View full text |Cite
|
Sign up to set email alerts
|

Relation of the A-B distinction and trust-distrust sets to addict patients' self-disclosures in brief interviews.

Abstract: In a study of interpersonal and situational determinants of self-disclosure in "resistive" patients, psychiatric aides conducted brief interviews with hospitalized narcotics addicts. Participants' A-B status and patients' preinterview sets to "trust" (TFH) or "distrust" (DHH) the aide comprised the manipulated factors in a 2 X 2 X 2 design (N = 40 male dyads). As expected, A-type aides with DHH patients and B-type aides with TFH patients obtained better patient self-disclosure in "personal" (as vs. neutral) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1972
1972
1978
1978

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…Also, with TAS patients, B-type interviewers outperformed As on total (p < .05) and neutral (p < .02) but not on personal topics. Taken together, these results offer substantial support to the interaction hypothesis and are also consistent with the findings of Berzins et al (1970) with addict patients, and those of Greene (1971) and Welch (1971) with Veterans Administration inpatients.…”
Section: Intrainterview Measuressupporting
confidence: 87%
See 2 more Smart Citations
“…Also, with TAS patients, B-type interviewers outperformed As on total (p < .05) and neutral (p < .02) but not on personal topics. Taken together, these results offer substantial support to the interaction hypothesis and are also consistent with the findings of Berzins et al (1970) with addict patients, and those of Greene (1971) and Welch (1971) with Veterans Administration inpatients.…”
Section: Intrainterview Measuressupporting
confidence: 87%
“…The finding that A-type interviewers sat closer to the patients than did Bs is consistent with the results of the Berzins et al (1970) study and of the Green (1971) and Welch (1971) studies, in which the A interviewer was rated 'as "warmer" than the B interviewer. Note, however, that this index of behavioral "approach" strikingly contra- Note.…”
Section: Intrainterview Measuressupporting
confidence: 86%
See 1 more Smart Citation
“…An Acceptability for Psychotherapy scale (46 items) measured the extent to which a patient's responses resemble those of male patients judged acceptable for psychotherapy by Lexington clinicians (Monroe & Hill,19S8). High scores on this scale also have predicted self-disclosure among male addicts in experimental interviews (Berzins, Ross, & Cohen, 1970;Berzins, Ross, & Monroe, 1970).…”
Section: Competence Indexesmentioning
confidence: 90%
“…Later analogue and therapy studies have generalized the earlier findings and suggested the relative superiority of As with schizoid and extropunitive individuals (Berzins, Ross, & Friedman, 1972;Berzins, Seidman, & Welch, 1970) and of Bs with intropunitive individuals . In studies by Carson, Harden, and Shows (1964) and Berzins, Ross, and Cohen (1970), work further removed from the original outcome studies has focused on the process involved and has demonstrated the greater effectiveness of As in eliciting personal information from distrustful subjects. Although such an ability was cited by Whitehorn and Betz to account for the greater effectiveness of the As with schizophrenics in their study, the later studies suggest wider applications of the A-B distinction beyond the traditional therapy situation to other helping relationships.…”
mentioning
confidence: 97%